All You (Still) Need Is Love? Love, Pain, and Capitalism in Contemporary Culture (KULT_online, 2013)
Eva Illouz's Why Love Hurts is the latest contribution to the ongoing attempt in Sociology, Cultural and Gender Studies to come to terms with modern forms of romantic love and emotional subjectivities in times of global capitalism and shifting gender relations. This book does “to love what Marx did to commodities”, that is, to show how love is “shaped and produced by concrete social relations” and “circulates in a marketplace of unequal competing actors” (p. 6). Illouz sketches how the social organization of love and pain have changed throughout modernity and have become subject to economic as well as gendered power dynamics in unprecedented ways. By outlining how the modern romantic self is caught in the attempt to reconcile competing discourses of egalitarianism, feminism, and individualism with the desire to love and be loved, this book ultimately argues that love has become one of the most important and most painful sites for the constitution of modern subjectivities.